Correlation Of Emulsifying Properties And Microcapsule Oxidative Stability In Microencapsulation By Spray Drying Method - Estiasih, Teti; Ahmadi, Kgs. (Jurnal Teknologi Pertanian, 2004)
This research was conducted to elucidate the correlation of protein emulsifying properties and microcapsule oxidative stability. These properties were analyzed in sodiuym caseinate stabilized triglycerieds enriched with w-3 fatty acids emulsions. Phospholipids was added to enhance these emulsifying properties. The results showed that emulsion stability index (ESI), refered to emulsion stability prior to drying, was correlated significantly with microcapsule oxidative stability. Other properties did not significantly correlated because of phospholipids addition that cahnged the emulsifying properties and film forming properties of microcapsule concomitantly. Keywords: protein emulsifying properties, microencapsulation, oxidative stability